Effect of V–III Ratio‐Based Growth Mode on the Surface Morphology, Strain Relaxation, and Dislocation Density of AlN Films Grown by Metal‐Organic Chemical Vapor Deposition. Issue 1 (4th September 2022) - Zhang, Li; Li, Junshuai; Deng, Xuguang; Xu, Kun; Zhou, Xin; Zhang, Xuan; Ma, Yongjian; Yang, Feng; Fan, Yaming; Zhang, Baoshun
Abstract : Herein, regulation of the growth mode through manipulating the V–III ratio during metal‐organic chemical vapor deposition (MOCVD) growth of AlN films on c ‐plane sapphire substrates and optimization of the crystalline quality and surface morphology of AlN films are demonstrated. Based on detailed analyses of the evolution process of surface morphology, dislocation annihilation, and stress state of the AlN film during MOCVD growth, it is found that 2D rather than 3D growth mode introduces tensile stress as well as promotes edge‐type threading dislocation (ETD) propagation and crack generation, while 3D growth mode produces rough surface. These results would help to further understand the AlN growth mechanism and provide important guidance on the preparation of AlN‐related epitaxial structure. Abstract : Based on detailed analyses of the evolution process of surface morphology, dislocation annihilation, and stress state of the AlN film during metal‐organic chemical vapor deposition (MOCVD) growth, it is found that 2D rather than 3D growth mode introduces tensile stress as well as promotes edge‐type threading dislocation (ETD) propagation and crack generation, while 3D growth mode produces rough surface.